HPTLC analysis of the essential oil from Pimenta dioica leaf - Priya S Rao,Sheth Navinchandra,K. N Jayaveera (Journal of Applied Pharmaceutical Science)
The present study was done with an aim to standardize the volatile oil obtained from the leaf of Pimenta dioica (Linn.) Merill, belonging to the family Myrtaceae, commonly known as 'Allspice', by HPTLC analysis. The leaves of P. dioica is traditionally being used as a dental analgesic. The present investigation reports the seasonal variation in the content of eugenol, in the leaf volatiles of Pimenta dioica thereby giving insight into the most favorable month for the collection of the drug. Volatile oils are primarily composed of terpenes, the composition of which may alter depending upon the availability of sunlight. The results reveal that the oil collected in April and July showed good content of eugenol.
Keywords: Pimenta dioica,Myrtaceae,Allspice,HPTLC,eugenol.